Mixed convection stagnation-point flow on vertical stretching sheet with external magnetic field - Md. Ali, Fadzilah; Nazar, Roslinda; Md. Arifin, Norihan; Pop, Ioan (Springer, 2014)
The problem of steady laminar magnetohydrodynamic (MHD) mixed convection stagnation-point flow of an incompressible viscous fluid over a vertical stretching sheet is studied. The effect of an externally magnetic field is taken into account. The transformed boundary layer equations are solved numerically by using an implicit finite-difference scheme. Numerical results are obtained for various values of the mixed convection parameter, Hartmann number, and Prandtl number. The effects of an externally magnetic field on the skin friction coefficient, local Nusselt number, velocity, and temperature profiles for both A > 1 and A < 1, where A is the velocity ratio parameter, are presented graphically and discussed in detail. Both assisting and opposing flows are considered, and it is found that dual solutions exist for the opposing flow.